Challenges in curbing misappropriation of assets and corruption in Malaysian local authorities / Rosmawati Haron - Haron, Rosmawati (2020)
The main objective of this research is to determine the challenges that fill in as barriers in the execution and implementation of Rule 4(2)(C) of the Public Officers (Conduct and Discipline) (Amendment) Regulations 2009 served in the Malaysian public sector. The rule, issued by the Public Service Department, specifically incorporates misappropriation of assets and corruption as punitive disciplinary offences to the public sector employees. Nevertheless, misappropriation of assets and corruption incidents remain significant. Being the motivations, by employing agency theory as the background, this research employed a combination of semi-structural interviews and open-ended survey involving 149 Malaysian local authorities. The responses from six semi-structured interviews and 199 open-ended survey were analysed, tabulated and themed, to capture the existing-experiences and being the descriptive data. The collected information enabled a comprehensive understanding on the behaviour gaps between government policy and its actual practices. Eleven main challenges were identified as the main concerning factors vis-à-vis fraud awareness: inefficient leader, attitude, weak enforcement, lack of internal strengths, ineffective training, lack of authority, opportunity due to lack of control, burden of proof due to bureaucracy, favouritism/ excessive discretions, organisational culture, and public perception. The findings also indicated that while participants were aware of corruption and misappropriation of assets occurring in their department, the matters were rarely reported. Subsequently, the perceived wrongdoing experiences of employees had become a blessed daily routine. Wherein the ambit of limitations of this study, the scope and findings contributed to the literature further insights into these holding ongoing matters of the local authorities shenanigans.